RANCANG BANGUN TOKO ONLINE BUKET BUNGA WISUDA “CRAFTTY SOLO” BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL - Putri Lestari; Firdhaus Hari Syahputra; Astri Charolina (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2019)
Craftty Solo is engaged in the sale of flower bouquets in graduation. The Marketing used social media such as Instagram, Whattshap and COD (Cash On Delivery). Therefore, the limitations product marketing is an obstacle in increasing sales turnover. The aim of this research is to create a online shop based on web of Craftty in expanding the marketing area. This study used waterfall method approach. This method is used to develop the system by a coherent step namely analysis, design, coding and testing. System design used Unified Modelling Language (UML). While, the testing system used the Webqual method. This research produces a website-based system in Craftty Solo. It has a menu of Home, Help, Contact Us, Bouquets and Dolls, Bouquet of flowers to facilitate the buying and selling process. Basides it also can expand the marketing area. Based on the results of testing system using Webqual method with 4 testing factors, namely Usability Quality, Information Quality, Interaction Quality and Overall, the results of total quality on website are 99.8%